Technology as a Weapon in Domestic Violence: Responding to Digital Coercive Control. Issue 3 (2nd July 2020) - Woodlock, Delanie; McKenzie, Mandy; Western, Deborah; Harris, Bridget
ABSTRACT: Technology-facilitated domestic violence is an emerging issue for social workers and other service providers. The concept of Digital Coercive Control (DCC) is introduced to highlight the particular nature and impacts of technology-facilitated abuse in the context of domestic violence. While practitioners have become more adept at working with women experiencing DCC, there is still little known about its dynamics and whether this violence requires a change in current service responses. This article explores findings from survey research conducted with 546 Australian domestic violence practitioners about the ways perpetrators use technology as part of their abuse tactics. The findings demonstrate that DV practitioners believe perpetrator use of technology is extensive and has significant impacts on the safety of clients. A major dilemma faced by practitioners is how to promote and facilitate client safety from DCC while still enabling safe use of technology so clients can remain connected to family, friends, and community. IMPLICATIONS The use of digital technology in domestic violence creates a significant practice issue for Australian domestic violence practitioners. The development of a practice framework for responding to digital coercive control may assist practitioners to highlight the risks posed by this abuse, while still enabling women and children the freedom to participate in the digital realm.